Blockchain-Enabled Decentralized Identity Management: A Novel Framework for Microservices Architecture - Bhaskara Garnimitta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a novel framework for implementing decentralized identity management in microservices architecture using blockchain technology. The proposed solution addresses the inherent challenges of traditional centralized identity management systems by leveraging distributed ledger technology and smart contracts to create a secure, transparent, and user-centric authentication mechanism. The framework incorporates comprehensive privacy controls and consent management features while ensuring compliance with regulatory requirements across various industries. Through extensive evaluation across multiple use cases in healthcare, financial services, and government sectors, the results demonstrate enhanced security, improved scalability, and better user privacy control compared to conventional approaches. The article suggests that blockchain-based identity management can significantly reduce the risk of security breaches while providing a more robust and flexible authentication mechanism for modern distributed systems. This article contributes to the growing body of knowledge in distributed systems security and provides practical insights for organizations looking to implement decentralized identity management solutions.